Effects of Low Temperatures on Nitrogen Uptake, Partitioning, and Use in Creeping Bentgrass Putting Greens. Issue 2 (9th February 2017) - Bauer, Samuel J.; Horgan, Brian P.; Soldat, Douglas J.; Lloyd, Daniel T.; Gardner, David S.
Abstract : Late‐fall nitrogen (N) fertilization is commonly recommended for turfgrass nutrition in the Upper Midwest, although research identifying its efficiency and subsequent benefit is lacking for creeping bentgrass ( Agrostis stolonifera L.). The objectives of this research were to evaluate the efficiency and agronomic benefits of late‐fall N applications on creeping bentgrass putting greens. Silt loam and sand putting greens were established with 'L‐93' creeping bentgrass 7 yr prior to this study in St. Paul, MN, and Madison, WI. Labeled 15 N ammonium sulfate was applied to inground lysimeters at rates of either 25 or 50 kg N ha −1 in mid‐October or mid‐November 2009, and a spoon‐feeding approach of 10 kg N ha −1 was applied in five equally spaced applications (totaling 50 kg N ha −1 ) between 25 Sept. and 15 Nov. 2009. The labeled 15 N was used to quantify uptake and partitioning to verdure and thatch in the late fall and spring. The same treatments were applied to main plots with unlabeled ammonium sulfate to evaluate use, as determined by turfgrass quality, chlorophyll index, clipping yield, and N concentration. Nitrogen fertilizer applied up to mid‐October increased quality, color, and yield prior to winter, while the benefit of mid‐November applications was not apparent until the following spring; higher N rates increased these effects. The greatest cumulative clipping yields were associated with all 50‐kg N ha −1 rates, and application timing was not a significant factor. Clipping N concentration increased following spoon‐feeding and October applications in the fall, indicating good transport of N fertilizer to shoots prior to winter. The efficiency of 25‐ and 50‐kg N ha −1 applications was similar under optimum weather conditions, but this efficiency was reduced in environments conducive to N loss and reduced plant uptake; precipitation, and cold temperatures. The most efficient use and consistent benefit was seen with the spoon‐feeding approach